Effect of Nutrient, Light Intensity and Temperature on the Growth Rates and Metabolism of a Stress-Resistant Bacillariophyta – Entomoneis sp. - in Izmir Bay (Aegean Sea) - ADALIOĞLU, SEZGI; ÇALIŞKAN, GÜLIZAR (Mediterranean Marine Science, 2020)
A unicellular marine microalga, Entomoneis sp. was isolated and studied as had become the dominant species according to other bacillariophyta species in different environmental fluctuations in Izmir Bay. Because of our effort to better understand the dynamics of this microalga that facilitates unprecedented domination, we conducted on a monoculture isolation study.In this study, experiments were planned with the annual range of the Izmir Bay temperature, and the demonstrated behavior of the species in light and nutrient conditions. The stock culture medium was illuminated by approximately 50μmol photons m-2s-1 of illumination with 14/24 daylight. The temperature of the climate chamber was set on the summer (T1 (21±1oC)), spring (T2 (17±1oC)) and winter (T3 (13±1oC)) of Izmir Bay. Experiments were also applied with four different light intensities (L1 (50 μmol photons m-2s-1), L2 (25 μmol photons m-2s-1), L3 (5 μmol photons m-2s-1) and L4 (dark)). In this context, nutrient measurements were made on samples of the exponential, stationary and death phase of the culture and nutrient analyses were carried out. The results, which were designed according to ceteris paribus assumptions, were adapted to Michaelis-Menten kinetics. Consequently, considering the lifetime of the diatom at different temperature conditions, T3 was determined as an optimum temperature. Maximum growth rate and process time were observed at this temperature. This is the evidence why these diatoms are available in the winter. Once the light intensity was increased, the growth rate was increased at the T1 and T2 temperatures. However, T3 had a high growth rate in the nearly L1 light intensity. Considering the consumption and transformation of different nutrient conditions, different results for both types of microalgae were obtained.